Schistosomiasis mapping in Senegal: from baseline to present - Kane, Ndeye M.; Sylla, Khadime; Sy, Ngayo; Diop, Boubacar; Monteil, Rose; Mané, Malang; Gueye, Daouda; Samb, Momadou L.; Diallo, Babacar Banda; Woo, Madeline; Ritter, Julie; Evans, Darin; et al. (Frontiers in Tropical Diseases, 2025)
IntroductionSchistosomiasis has been a major public health concern in Senegal for almost 40 years. Mass drug administration (MDA) is the primary control strategy for treating schistosomiasis, however, there is a global limited availability of praziquantel therefore not all at-risk groups can be adequately treated. For settings in Senegal where there are numerous permanent bodies of water and persistent water contact, reducing prevalence and maintaining progress is challenging as reinfection occurs rapidly and can quickly return to pre-treatment levels. MethodsIn this paper we compare schistosomiasis prevalence following nearly 10 rounds of MDA. We also explore the impact of shifting decision-making from district-level prevalence to sub-district level prevalence on endemicity categorization and drug needs. ResultsUsing mapping survey data from baseline (1996-2013) to the most recent impact assessment (2022-2024) we found that schistosomiasis prevalence declined significantly from 19.3% to 14.4%. Analysis of changes in endemicity categorization by district and sub-district level prevalence found that a larger percentage of sub-districts were classified as non-endemic, and a lower percentage of sub-districts were low or moderate/high endemicity compared to using district-level prevalence. ConclusionThese differences suggest that shifting from treating entire districts to targeting sub-districts may yield similar outcomes to current strategies while offering economic and drug resource allocation benefits. This information is valuable for governments, donors, and implementation partners involved in the planning and execution of MDA programs in these regions.